Analisis Tingkat Penerimaan Sistem E-Learning menggunakan Blog Gratis sebagai Alternatif Media Pembelajaran pada Guru - Amalia, Faizatul; Brata, Adam Hendra; Sulistyo, Rizki Tri; Diofanu, Andre (Jurnal Teknologi Informasi dan Ilmu Komputer, 2018)
Blog is a medium used to post news, information, video-based websites. The types of blogs that exist today are paid or free of charges such as Blogspot, WordPress, and others. Currently, blog users are numerous. This is because the function of the blog not only for posting news or information but the reader can provide advice related to the content or ask the blogger. In the world of education, blogs can be used as a medium of learning that can help post the subject matter, daily repetition announcements, or discussion related subject matter. But the use of the blog as a learning medium is less visible. This research has some intentions are: discovering the percentage of teachers which is used a free blog as an alternative learning media, discovering what factors are influenced in accepting the technology of free blog, and implementing the UTAUT method to evaluate in accepting technology in free blog as an alternative learning media. The method of UTAUT (Unified Theory of Acceptance and Use of Technology) is used to test the acceptance of technology by the user against the use of blog as a medium of learning in school. The Vocational Teachers of Malang are being used in this research as a population. From this population, we should use the sampling method. And the sampling method is used random sampling which is 61 samples from all of the teacher in Vocational School in Malang. The result from this research are: (1) Blogspot is the most used by teacher in vocational school as learning media is about 63%, then wordpress is about 18.5%, Edmodo is about 17.4% and other is about 1.1%; (2) and at about 94.02% in effort expectancy, 89.50% in performance expectancy, 88.04% in social influence, 86.04% in supporting facilities, 85.71% in use behavior, and 84.39% in behavioral intention.